2000
DOI: 10.1177/039139880002300207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Metabolism of Medium-and Plasma Perfused Primary Pig Hepatocytes Cultured around a 3-D Membrane Network

Abstract: Culture media are frequently used in the evaluation of metabolical functions of hepatocytes in hybrid liver support systems (hLSS). However, media compositions differ substantially from those of plasma. Therefore, our study was designed to investigate whether current in vitro studies with medium are suitable to assess the metabolical competence of hLSS-cultures during clinical application as well as to explore whether the cell nutrition with medium provides a suitable modus operandi for stand by cultivation. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The model predicts that the kinetic constant of the MEGX further biotransformation (i.e., k 2, A , k 2, B ) decreases in time faster than that of MEGX formation from lidocaine (i.e., k 1, A , k 1, B ). This causes the shift towards longer t max and eventually causes the MEGX concentration profile to lose its typical bell shape with downward concavity as cells die off in adhesion culture, as shown in Figure 5 and Figure 8 [ 18 ]. Maintenance of a good liver cell state and competence in the bioreactor is possibly permitted by the favorable cell microenvironment produced by the controlled intermembrane spaces enabled by the orderly membrane arrangement and by the bleed/feed perfusion mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model predicts that the kinetic constant of the MEGX further biotransformation (i.e., k 2, A , k 2, B ) decreases in time faster than that of MEGX formation from lidocaine (i.e., k 1, A , k 1, B ). This causes the shift towards longer t max and eventually causes the MEGX concentration profile to lose its typical bell shape with downward concavity as cells die off in adhesion culture, as shown in Figure 5 and Figure 8 [ 18 ]. Maintenance of a good liver cell state and competence in the bioreactor is possibly permitted by the favorable cell microenvironment produced by the controlled intermembrane spaces enabled by the orderly membrane arrangement and by the bleed/feed perfusion mode.…”
Section: Discussionmentioning
confidence: 99%
“…If deemed useful, lidocaine in the adsorbed phase could be predicted by the model for the best-fit parameter values. Experimental data previously reported [ 18 ] were included in the analysis. Lidocaine binding to serum proteins was accounted for with an unbound lidocaine fraction fu = 0.65 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Matrix is an important part of affecting hepatocytes function. Many researches showed that collagenous matrix could provides an environment that more closely resembles that in vivo and allows to maintain the expression of certain liver-specific function of hepatocytes [44][45][46][47] . In this study, the hepatocytes keep their biological characters well after storage in liquid nitrogen for 4 mo.…”
Section: Discussionmentioning
confidence: 99%
“…The filter was kept at room temperature under light exclusion until reuse and after priming the filter with normal saline that contained an in vitro dosage of antibiotics proven to be effective in maintaining sterile conditions and membrane functionality in hollow fiber bioreactors (penicillin 100 IU/ml and streptomycin 100 mg/ml). 18 Another 10 l of normal saline was used to extensively rinse the filter again just before priming for a second time with blood for CT measurement. Blood priming was performed in single-pass mode and the system was operated with blood flow and filtration rates similar to the first experiments.…”
Section: Renal Replacement Therapy In Vitro Circuitmentioning
confidence: 99%